Selective Extraction and Purification of Papain Using Polyethylene Glycol (PEG 4000)/Potassium Citrate Aqueous Two Phase - Lu, Yanmin (Asian Journal of Chemistry, 2014)
Mathematical models concerning the purification of papain from the crude papain in an aqueous two-phase system which are composed of polyethylene glycol (PEG 4000)/potassium citrate are established with response surface methodology. The concentration of PEG 4000 and potassium citrate, the concentration of additional salt (KCl), the temperature and pH on the papain purification have been investigated. Results showed that papain tends to partitions to the more hydrophilic salt-rich phase. The steepest ascent method was used to locate the optimal domain. Papain was successfully extracted to the bottom phase of a system composed of 15 % (w/w) PEG 4000, 17 % (w/w) citrate and 5.0 % (w/w) KCl at pH 5.0 and 30 °C. Under those conditions, the specific activity, purification factor and activity yield for papain were 1703.02 U/mg, 1.89 and 94 %, respectively. The purity of extracted papain was confirmed by SDS-PAGE analysis.